Perancangan Aplikasi Adopsi Kucing dengan Framework ReactJS dan Pendekatan Agile Berbasis Analisis PIECES - Meyliana, Anastasia; Kurniawati, Brilliannissa Zulfa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The increasing population of stray cats in urban areas demands innovative solutions to support a more efficient and transparent adoption process. This study aims to develop a web-based cat adoption application using the ReactJS framework and the Agile approach. In the development process, PIECES (Performance, Information, Economy, Control, Efficiency, and Service) analysis is used to identify system requirements and evaluate application performance. The Agile method is applied to enable iterative and adaptive development according to user needs. The ReactJS framework was chosen because of its ability to build responsive and interactive user interfaces. This application is equipped with cat gallery features, adoption profiles, adoption status tracking, online donations, and volunteer registration. The test results show that the developed application is able to increase the efficiency of the adoption process by up to 40%, increase user satisfaction based on the User Experience Questionnaire (UEQ), and support transparency in shelter management through donation and volunteer management features. PIECES analysis provides important insights to improve the performance and service aspects of the application. This application not only simplifies the adoption process but also increases public awareness of animal welfare equipped with adaptive and user-based features that integrate technology to support more effective and sustainable animal adoption.